ELITE PRIMORDIALITY AND REGRESSIVE NATION BUILDING IN NIGERIA: A STUDY IN PREBENDALISM - ABAGEN, Franc Ter (Socialscientia: Journal of Social Sciences and Humanities, 2018)
Nigeria’s peculiar political and socio-economic history has illustrated the process of nation building albeit as an arduous and challenging task. The reality of the Nigerian polity is that it is a curious amalgam of a multiplicity of diverse ethnic groups and religious persuasions. It is the Elite from these groups that have continuously championed the primordial and prebendalist orientations of the populace in matters of resource allocations at the national level. Indeed there exists a curious link between primordiality and prebendalist alignments as the basis for Nigeria’s regressive nation building profile. This paper hinged on the use of Social Practice Theory also utilizes textual analysis from secondary data sources. The prominence of primordial and prebendalist convictions has consequently led to the consistent polarization of the component sectors of the polity. This in turn has made the attainment of a united, progressive, cohesive and cooperative nation state almost impossible. The perpetuation of these ideologies is responsible for the constant rivalry, conflict and failure of the Nigerian state to achieve the desired level of nation building. This situation has rather created a polity with a regressive nation building culture with very grim implications for future existence. It is therefore recommended that political elite engages a new reorientation towards progressive nation building values and complimentary ones that ensure and promote unity and a common identity in order to reverse the ominous trend.